2019
DOI: 10.1111/jfd.12960
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals the role of p53 signalling pathway during red‐spotted grouper nervous necrosis virus infection in Lateolabrax japonicus brain cells

Abstract: Nervous necrosis virus (NNV) is one of the fish pathogens that have caused mass mortalities of many marine and freshwater fishes in the world. To better comprehend the molecular immune mechanism of sea perch (Lateolabrax japonicus) against NNV infection, the comparative transcriptome analysis of red‐spotted grouper nervous necrosis virus (RGNNV)‐infected or mock‐infected L. japonicus brain (LJB) cells was performed via RNA sequencing technology. Here, 1,969 up‐regulated genes and 9,858 down‐regulated genes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In another study also performed with DLB-1 cells, the transcriptomic profiles obtained from European sea bass head-kidney leucocytes incubated with NNV infected and uninfected cells were very similar, supporting that cell-mediated cytotoxic activity in sea bass is not primed upon NNV infection [231]. Other cells used for transcriptome analysis were Asian seabass (Lateolabrax japonicus) epithelial cells (SB) [229], grouper kidney (GK) cells [228] and Lateolabrax japonicus brain cells (LJB) [233]. The assembly of the transcriptome of NNV-infected SB cells, as in the previously described cell lines, showed a strong induction of various genes relevant to innate immunity which were identified as receptor-transporting 3 (RTP3), Viperin, IRF3, IFN and two heat shock protein (HSP) family members (Hsp30 and 70) [229].…”
Section: Host Responsementioning
confidence: 82%
See 2 more Smart Citations
“…In another study also performed with DLB-1 cells, the transcriptomic profiles obtained from European sea bass head-kidney leucocytes incubated with NNV infected and uninfected cells were very similar, supporting that cell-mediated cytotoxic activity in sea bass is not primed upon NNV infection [231]. Other cells used for transcriptome analysis were Asian seabass (Lateolabrax japonicus) epithelial cells (SB) [229], grouper kidney (GK) cells [228] and Lateolabrax japonicus brain cells (LJB) [233]. The assembly of the transcriptome of NNV-infected SB cells, as in the previously described cell lines, showed a strong induction of various genes relevant to innate immunity which were identified as receptor-transporting 3 (RTP3), Viperin, IRF3, IFN and two heat shock protein (HSP) family members (Hsp30 and 70) [229].…”
Section: Host Responsementioning
confidence: 82%
“…In recent years, a great deal of progress has been made on high-throughput tools for sequencing the transcriptome (RNA-Seq), enabling genome-wide transcriptomic analysis and providing valuable information for understanding virus-host interactions [227]. Different transcriptomic analyses have been performed on both NNV-infected cells [228][229][230][231][232][233] and fish [234][235][236][237][238].…”
Section: Host Responsementioning
confidence: 99%
See 1 more Smart Citation
“…As seen in the DLB-1 cell line, RGNNV infection of L. japonicus brain cells (LJB) resulted in immune response regulation and apoptotic-related proteins' transcription (e.g., ISG15, IRFs, TLRs, HSPs) to assist the virus in escaping the host antiviral response. In the same study, the p53 signaling pathway was shown to be repressed by down-regulation of p53 and its downstream target genes (BAX, CASP8, CytC) and by up-regulation of its negative regulators MDM2 and MDM4 [40]. The p53 signaling pathway repression has a dual effect in the viral response by inhibiting the innate antiviral immunity and the type I IFN response, and the virus-infected cells apoptosis [120], thus promoting virus replication in RGNNV-infected LJB cells and facilitating the transmission of newly formed viral particles to other cells.…”
Section: Cell Linesmentioning
confidence: 86%
“…In order to take a closer look at the effects of nodavirus in infected fish, several studies have focused on the transcriptome profiling of in vitro infected cells. Such investigations have been performed in brain cell lines of European sea bass (DLB-1 cell line) [43] and Lateolabrax japonicus (LJB cells) [40,51], in grouper kidney cells (GK cell line) [30], in European sea bass head-kidney leukocytes [37], and in Asian sea bass epithelial cells (SB cell line) [35]. Similar studies were performed in ZF-4 cells, an embryonic-derived zebrafish cell line [34], in striped snakehead fish cells (SSN-1) [36], and in orange-spotted grouper (Epinephelus coioides) fin cells [39].…”
Section: Cell Linesmentioning
confidence: 99%